Enhancing routine immunization efforts for older adults and frail individuals: Good practices during the SARS-CoV-2 pandemic in Italy - Andrea Poscia; Giulia Paolorossi; Agnese Collamati; Claudio Costantino; Daniel Fiacchini; Claudio Angelini; Roberto Bernabei; Daniela Cimini; Giancarlo Icardi; Andrea Siddu; Andrea Silenzi; Antonietta Spadea; et al. (Taylor & Francis Group, 2024)
ABSTRACTInfectious diseases pose a significant burden on the general population, particularly older adults who are more susceptible to severe complications. Immunization plays a crucial role in preventing infections and securing a healthier aging, but actual vaccination rates among older adults and frail individuals (OAFs) remains far from recommended targets. This study aims to collect and share good practices implemented in several Italian local health districts during the SARS-CoV-2 pandemic to ease routine immunization for OAFs. A 28-items questionnaire has been developed to collect information on organization aspect of immunization services and local good practices implemented before and during the SARS-CoV-2 pandemic. Twelve Public Health managers representative of 9 Italian Regions were further interviewed between January and March 2021. Despite literature suggests several effective interventions to increase vaccine demand, improve vaccine access, and enhance healthcare providers' performance, our survey highlighted substantial heterogeneity in their implementation at local level. Seven good local practices have been identified and described: mass vaccination centers; vaccination mobile units; drive-through vaccination; co-administration; tailored pathways; cooperation among providers involved in vaccination; digitization. Our survey pointed out valuable strategies for enhancing routine immunization for OAFs. Providers should combine effective interventions adequate to their specific context and share good practices.